Association Analysis of MMP-13 (rs2252070) Gene Polymorphism and the Susceptibility to Chronic Periodontitis - Chatterjee, Shubhangini; Rajasekar, Arvina (Curēus (Palo Alto, CA), 2024)
Chronic periodontitis is a multifactorial inflammatory condition influenced by genetic factors. Matrix metalloproteinase (MMP)-13, serving as a crucial enzyme involved in extracellular matrix remodeling, is associated with the degradation of periodontal tissues. Therefore, this study assesses the genetic link between the MMP-13 (rs2252070) genetic variation and chronic periodontitis in a Southern Indian demographic. The study was conducted at Saveetha Dental College in Chennai, India. It involved a total of 100 subjects, 50 individuals affected with periodontitis (classified as stage II and above, American Association of Periodontology 2018 criteria) and 50 individuals who were periodontally healthy or were diagnosed as having mild gingivitis. We isolated DNA from the blood samples obtained from the participants. Specific primers that flank the BsrI region of the MMP-13 receptor gene were used in the process of DNA amplification. Subsequently, a restriction fragment length analysis using the BsrI enzyme was carried out for genotyping of the amplicon. Based on the restriction fragment length polymorphism pattern, we obtained certain genotypes. These were further recorded and followed by statistical analysis. We conducted a chi-square test to draw a comparison in terms of their genotype and allele frequencies. We calculated the odds ratio, along with 95% confidence intervals. The frequency of genotypes and distribution of MMP-13 polymorphism did not exhibit a statistically significant difference at χ2 degrees of freedom (P = 0.913). We inferred from our study that there was no significant difference between the groups concerning homozygous and heterozygous mutant genotypes (AA vs. AG + GG), with a P-value of 0.6871. The observed frequencies of GG (47% vs. 43%) and AG+AA (41% vs. 42%) genotypes did not indicate a significant difference between the groups. Similarly, there was no noteworthy distinction between the A allele (62% vs. 65%) and G allele (38% vs. 35%) in the case and control groups. The findings of the study reveal that there is no correlation between MMP-13 (rs2252070) gene polymorphism and periodontitis.